Chemical constituents and larvicide potential against Aedes aegypti of the essential oil of the Origanum vulgare L. (Research, Society and Development, 2021)
Essential oils extracted from medicinal plants have been shown to be an alternative in the search for natural larvicides. Thus, the present study aimed to evaluate the larvicidal activity of essential oil extracted from the leaves of Origanum vulgare L. leaves. The essential oil was extracted by hydrodistillation at 100°C for 3 h, with chemical characterization through Gas Chromatography coupled to mass spectrometry (CG-MS). Then, the lethality of the essential oil against Aedes aegypti was evaluated, and the LC50 was calculated for the action of the essential oil from the Probit method. The major constituents found in the essential oil of O. vulgare were Timol (72.14%) and p-cymene (12.25%). The larvicidal activity of the essential oil presented the LC50 of 31.66 mg L-1. The results indicate that the evaluated essential oil is composed of substances that provide a good larvicidal effect, revealing its efficiency in combating and controlling Aedes aegypti.